Selective packaging of mitochondrial proteins into extracellular vesicles prevents the release of mitochondrial DAMPs - Kiran Todkar (Nature Portfolio, 2021)
Mitochondrial content in extracellular vesicles (EVs) can enhance inflammation, although its role in noninflammatory conditions is unclear. Here, the authors show that mitochondria-derived vesicles target material to EVs, whereas Parkin directs damaged mitochondrial content to lysosomes, providing insight into mitochondria-driven immune responses.